Extracellular Vesicles in Pathogenesis and Treatment of Metabolic Associated Fatty Liver Disease - Sun, Ji; Zhang, Dianbao; Li, Yiling (Frontiers in Physiology, 2022)
Metabolic associated fatty liver disease (MAFLD) is the most common chronic liver disease worldwide due to the sedentary and overeating lifestyle. However, the pathophysiology of MAFLD is still unclear and no drug was approved for MAFLD treatment. Extracellular vesicles (EVs) are heterogenous membrane-bound particles released from almost all types of cells. These nano-sized particles mediate intercellular communication through their bioactive cargos including nucleic acids, proteins, and lipids. The EVs modulate the metabolic homeostasis via communication between adipose tissue and liver. The dysregulation of lipid metabolism leads to inflammation in liver and the number and compounds of EVs were changed during MAFLD. The injured hepatocytes secrete EVs to induce the migration of bone marrow-derived monocytes and the activation of macrophages in liver. The EVs secreted by different cells regulate the alteration of hepatic stellate cell (HSC) phenotypes and HSC activation gives rise to liver fibrosis. Based on the participation of EVs in MAFLD progression, we discuss the prospects of EVs as a therapeutic target and their application in drug delivery